2015
DOI: 10.1111/peps.12109
|View full text |Cite
|
Sign up to set email alerts
|

Are Workplace Friendships a Mixed Blessing? Exploring Tradeoffs of Multiplex Relationships and their Associations with Job Performance

Abstract: Theory and research note the ubiquity of multiplex workplace friendships—multifaceted relationships that superimpose friendship with work‐focused interactions—but it is unclear how they compel or hinder job performance. In a study of insurance company employees (n = 168), we found that the number of multiplex workplace friendships in one's social network is positively associated with supervisor ratings of job performance. However, we also found that there is a negative indirect effect on job performance throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
231
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(264 citation statements)
references
References 188 publications
(339 reference statements)
5
231
0
2
Order By: Relevance
“…Individuals may seek out interactions at work for other reasons beyond daily PA, for example, after experiencing NA, incivility, or fulfilling their need to belong. Moreover, even enjoyable interactions can have a negative side due to friendship maintenance responsibilities (Methot et al, ), which may detract from engagement and subsequent performance. Our research only whets the appetite for more research into workplace interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals may seek out interactions at work for other reasons beyond daily PA, for example, after experiencing NA, incivility, or fulfilling their need to belong. Moreover, even enjoyable interactions can have a negative side due to friendship maintenance responsibilities (Methot et al, ), which may detract from engagement and subsequent performance. Our research only whets the appetite for more research into workplace interactions.…”
Section: Discussionmentioning
confidence: 99%
“…A further unique feature of this study is the mediating effect of engagement in the relationship between positive interactions at work and recovery experiences. The role of social mechanisms has only recently begun to be recognized (Heaphy & Dutton, 2008;Methot et al, 2016), and, as the current evidence suggests, they are integral in the recovery process.…”
Section: Research Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the social networks connecting the participants could have biased the results. (Fieseler, Meckel, & Ranzini, 2015), or to describe the need for social intranet systems that allow employees to get to know each other professionally and personally (Methot et al 2016).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…As argued above, the fourth theoretical implication is the consideration of both role response expectations and relationships. Scholars have indicated that not all high‐quality work relationships will guarantee expected and desirable outcomes (Bridge & Baxter, ; Methot, LePine, Podsakoff, & Christian, ). Here, we demonstrate that these conflicting characteristics of relationship quality have joint effects with role response expectations that affect cross‐domain communication and its role in resource loss and gain.…”
Section: Discussionmentioning
confidence: 99%